What Causes the Price of Gold to Fluctuate? Exploring the Factors Behind Fluctuations in Gold Prices (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This analytical paper begins by ascertaining the story of gold and why it is considered as one of the most valuable metal since centuries. The various uses of gold are listed and discussion has been made about the beginning and doom of the gold standard. Further, various factors contributing towards the continuously escalating prices of gold in India have been explored. The period from 1985 to 2015, has been considered for the purpose of trend analysis to get a better idea of why gold prices fluctuate and each factor has been individually dealt with both in terms of the intuitive relationship and actuals.